Psychopathology in female offenders of terrorism and violent extremism: a systematic review - Rakhshandehroo, Sadaf; Duits, Nils; Bergman, Dick; Verkes, Robbert-Jan; Kempes, Maaike (Frontiers in Psychiatry, 2023)
Introduction Terrorism and violent extremism are major social threats worldwide and are committed not only by men but also by women. Previous research has shown indications of psychopathology, among other personal and contextual factors, as a potential risk factor for perpetrating terrorist and violent extremist crimes. Despite the fact that women have engaged in acts of terrorism and violent extremism throughout history, the vast majority of literature on psychopathology so far has been mainly focused on men with terrorist and violent extremist behavior. As women's engagement in terrorism and violent extremism is increasing, and gender differences in psychopathology in offenders of terrorism or violent extremism may exist based on empirical evidence for such differences in offenders of violence, gender-informed research into psychopathology as a potential risk factor for offending is of pivotal importance for improving the effectiveness of counter-terrorism interventions. The present systematic review was designed to examine what empirical knowledge exists on the presence and potential contributing role of psychopathology in female perpetrators of terrorism or violent extremism. Methods A literature search was conducted to identify primary source studies in PsycINFO, PubMed, Embase, Web of Science, and Sociological Abstracts. ASReview as an artificial intelligence software was used to screen references. Results In total, eight studies were included, of which only two studies distinguished prevalence rates and types of psychopathology separately for women, indicating personality disorder as most common. All four out of the eight studies that reported on the relationship between psychopathology and terrorism and violent extremism assumed psychopathology to be a contributing factor in engaging in terrorist or violent extremist acts. However, none of these four studies reported on potentially present female-specific mechanisms of the role of psychopathology in offenses. Discussion The present systematic review draws the striking conclusion that there is a lack of clearly described empirical studies on psychopathology in female perpetrators of terrorism and violent extremism and emphasizes the importance of more future empirically based inquiries on this topic by the forensic psychiatric field. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=275354, identifier: CRD42021275354.